Finite element electro‐thermal modelling of nanocrystalline phase change elements using mesh‐based crystallinity approach. Issue 2 (1st January 2014) - Trombetta, M.; Williams, N.E.; Fischer, S.; Gokirmak, A.; Silva, H.
Abstract : Phase change memory cells composed of nanocrystalline Ge2 Sb2 Te5 with a heater diameter of 10 nm and Ge2 Sb2 Te5 thickness of 100 nm are studied by using two‐dimensional finite element simulations with COMSOL Multiphysics. The nanocrystalline Ge2 Sb2 Te5 is emulated by using a mesh‐based model incorporating crystalline grains of random size and location embedded in the amorphous media. The material parameters are modelled with temperature dependency from 300 to 1000 K, including electrical resistivity, thermal conductivity, electric field breakdown and Seebeck coefficient. This model is shown to capture the cycle‐to‐cycle and device‐to‐device variability in phase change memory cells.